PENGARUH KEMAMPUAN BERPIKIR LOGIS DAN LITERASI DIGITAL TERHADAP KEEFEKTIFAN PELAKSANAAN PRAKTIK KERJA LAPANGAN SISWA SMK - Hartanti Dwi Anggraini; Nurhasan Hamidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine and provide empirical evidence regarding the effect of logical thinking skills and digital literacy on the effectiveness of students' internship implementation (PKL). This research utilized a quantitative design with an associative survey approach. The population and sample of this study were 108 twelfth-grade students of the accounting program at SMK Negeri 6 Surakarta, selected using a saturated sampling technique (census). Data were collected through a test instrument to measure the logical thinking skills variable, and a Likert scale questionnaire to measure the digital literacy and internship implementation effectiveness variables. Data analysis was conducted using a multiple linear regression statistical test with the assistance of SPSS software version 25.0. The results showed that: (1) There is a positive effect of logical thinking skills on the effectiveness of internship implementation partially; (2) There is a positive effect of digital literacy on the effectiveness of internship implementation partially; and (3) There is a positive effect of logical thinking skills and digital literacy simultaneously on the effectiveness of internship implementation.